Analyzing intersectoral convergence to improve child undernutrition in India: Development and application of a framework to examine policies in agriculture, health, and nutrition - Ved, Rajani; Menon, Purnima (International Food Policy Research Institute, 2012)
India’s record of undernutrition presents a stubborn challenge. Given the multiple determinants of child undernutrition, effective action to tackle this problem in India and globally requires a range of inputs across various sectors. Delivering nutrition-specific and nutrition-sensitive interventions to entire populations requires that these various sectors come together at critical points and in meaningful ways to ensure delivery of key nutrition-related actions for communities and households. However, currently in India, a major challenge is bringing sectors together to deliver for a common goal. Although the lack of convergence is well documented, there lingers a substantial gap in articulating what needs to be assessed to ensure that convergence is indeed happening, or not happening. In an effort to close this gap, in this paper we describe a possible framework to enable convergence across sectors for action on nutrition. Our framework notes that issues related to convergence must be resolved in relation to three major steps in the policy process: policy formulation, implementation, and monitoring and evaluation. We articulate here questions related to convergence that must be asked at each of these stages of the policy process. We also conduct a desk review to analyze health and nutrition policies in India for evidence of attention to these aspects of convergence.